2014
DOI: 10.1007/s40136-014-0058-5
|View full text |Cite
|
Sign up to set email alerts
|

The Psychology of Facial Disfigurement: Implications for Whole Face Transplantation

Abstract: A decade has passed since the publication of the first report from the Royal College of Surgeons in England Working Party on Face Transplantation. Based on evidence available at the time, this report concluded that it was unwise to proceed with whole face transplantation (WFT). Since then, in the region of 20 WFTs have been performed. Data relating to the post-procedural psychological adjustment of a small number of patients are available and further studies have explored the psychological profiles of patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…Além das preocupações relacionadas à imagem, estudos enfatizam que os receptores também podem experimentar ansiedade constante devido ao medo da rejeição do enxerto. Essa questão destaca ainda mais a importância de um acompanhamento contínuo com uma equipe multidisciplinar (Rumsey, 2014).…”
Section: Metodologiaunclassified
“…Além das preocupações relacionadas à imagem, estudos enfatizam que os receptores também podem experimentar ansiedade constante devido ao medo da rejeição do enxerto. Essa questão destaca ainda mais a importância de um acompanhamento contínuo com uma equipe multidisciplinar (Rumsey, 2014).…”
Section: Metodologiaunclassified
“…Therefore they too require support and counselling throughout this process. 2,11,13 As increasing evidence emerges on the cosmetic end-outcomes of facial transplant patients, it has been reported that patients tend to acquire a hybrid appearance incorporating their existing facial features with that of the donor, with the underlying bony skeleton of the recipient contributing far greater to the overall appearance. 3,12,14,15 Allowing recipients to visualise what their appearance may resemble following the procedure has been made possible in some centres through the use of technology such as advanced three-dimensional (3D) imaging.…”
Section: Patient Considerationsmentioning
confidence: 99%
“…Interestingly, psychological adjustment could not be fully predicted by etiology and severity of disfigurement [ 4 ]. Good predictors of adjustment are psychosocial factors, such as perceptions of social support and acceptance as well as self-perceived appearance [ 4 , 6 , 7 ]. Therefore, specialists involved in ocular rehabilitation, such as ocularists, prosthetists, or maxillofacial prosthodontists, are required to have competence in the management of both physical and psychological difficulties in these patients.…”
Section: Introductionmentioning
confidence: 99%